2010
DOI: 10.1016/j.jallcom.2010.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural evolution during the annealing of an extruded AZ31 magnesium alloy

Abstract: a b s t r a c tMicrostructural evolution during the annealing of AZ31 extruded rod at 400 • C has been examined by employing neutron diffraction and electron backscatter diffraction (EBSD). In the as-extruded bar, equiaxed grains smaller than 5 m and large elongated grains having significant degrees of internal misorientation are oriented mainly with < 1 01 0 > parallel to the extrusion direction. Rapid grain growth occurs within the 180 s annealing period at 400 • C at the expense of the small grains with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(39 citation statements)
references
References 24 publications
1
37
1
Order By: Relevance
“…Yi et al [24] have previously seen a similar change of texture in AZ31 alloys as a result of annealing after extrusion. They have reported that the texture component in the IPF moves from the (10-10) to the (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) corner with increasing post-annealing time.…”
Section: Lattice Resistancementioning
confidence: 58%
“…Yi et al [24] have previously seen a similar change of texture in AZ31 alloys as a result of annealing after extrusion. They have reported that the texture component in the IPF moves from the (10-10) to the (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) corner with increasing post-annealing time.…”
Section: Lattice Resistancementioning
confidence: 58%
“…The development of a texture with a 11.0 component has been observed by various authors as a result of the growth of recrystallised grains in conventional Mg-Al-Zn alloys [8,34]. It can be a result of DRX if fully recrystallised microstructures are achieved [9,35] or the result of static recrystallisation (SRX) [8].…”
Section: Recrystallisation Mechanismsmentioning
confidence: 99%
“…It can be a result of DRX if fully recrystallised microstructures are achieved [9,35] or the result of static recrystallisation (SRX) [8]. In Fig.…”
Section: Recrystallisation Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations